Dynamics of Marenzelleria spp. Biomass and Environmental Variability: A Case Study in the Neva Estuary (The Easternmost Baltic Sea) - Sergey M. Golubkov; Mikhail S. Golubkov (Biology)
Predicting which non-indigenous species (NISs) will establish persistent invasive populations and cause significant ecosystem changes remains an important environmental challenge. We analyzed the spatial and temporal dynamics of the entire zoobenthos and the biomass of Marenzelleria spp., one of the most successful invaders in the Baltic Sea, in the Neva estuary in 2014–2023. A considerable decrease in Marenzelleria biomass was observed in the second half of the study period, which was accompanied by a sharp increase in the dominance of opportunistic oligochaete and chironomid species. Our one-way analysis of variance showed that communities with high Marenzelleria biomass had significantly higher diversity and biomass of native benthic crustaceans compared to communities with low alien polychaetes biomass. A high biomass of Marenzelleria was observed in biotopes characterized by low temperatures, high salinity, low plankton primary production and chlorophyll concentration. The results of PCA and one-way ANOVA indicated that these factors significantly influenced the spatial and temporal dynamics of the polychaete biomass. More detailed studies of the responses of NISs to environmental variables are needed to better understand and anticipate their dynamics in different regions of the Baltic Sea in relation to climate warming and anthropogenic impacts.